Molecular and Parasitological Survey of Bovine Piroplasms in the Black Sea Region, Including the First Report of Babesiosis Associated with Babesia divergens in Turkey - Aktas, M.; Ozubek, S. (Oxford Univ Press Inc, 2015)
Clinical cases of babesiosis were evaluated, and the frequency of bovine Babesia and Theileria parasites was determined in cattle. Blood samples and thin blood smears were collected from 23 cattle exhibiting clinical signs of babesiosis. In addition, tick and blood samples were collected from 100 apparently healthy cattle cograzing from the same area. Egg masses obtained from fully engorged female ticks were included. DNA isolated from blood and tick samples was screened for Babesia and Theileria by reverse line blot assay. Piroplasms compatible with Babesia spp. were observed microscopically for symptomatic cattle as circular, oval, elongated, or pear-shaped bodies. Parasitemia ranged from 0.08 to 0.9% for Babesia bovis, 2.5 to 15.4% for Babesia bigemina, and 7.4% for Babesia divergens. Reverse line blot showed positivity in 13 (13%) of the sampled clinically normal cattle and revealed the presence of three Babesia species. Babesia bovis was the most prevalent (9/100, 9%), followed by Babesia occultans (3/100, 3%) and B. bigemina (1/100, 1%). One animal infected with B. bigemina was also infected with B. bovis. The single animal infected with B. divergens showed symptoms of babesiosis. Ticks were identified as Rhipicephalus annulatus, Rhipicephalus turanicus, and Ixodes ricinus. One female R. annulatus and its egg mass were infected with B. bigemina. Neither Theileria annulata nor Theileria buffeli/orientalis infections were observed in cattle or ticks. This is the first report of clinical babesiosis caused by B. divergens in cattle from Turkey.
Keywords: Babesia; PCR; reverse line blot; cattle